Pengembangan Media Praktikum Laboratorium Virtual untuk Pembelajaran Optika Kelas VIII SMP Negeri 1 Tungkal Ulu - Henlenti Henlenti; Syamsurizal Syamsurizal; Rayandra Asyhar (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
Lab activity is necessary in studying science especially physics. It is needed to support theoretical teaching activity in the classroom. Lab plays important roles in physics teaching-learning activities. The facts, many schools have inadequate lab facilities to support lab works and thus limited lab activities can be done. To improve physics teaching-learning activities with limited lab facilities, virtual lab is necessary to be developed to ensure that theoretical teaching materials are supported by lab activity in virtual manner. The purpose of this study was to develop virtual lab for subtopic of optics. Students’ responses on the virtual lab were obtained through small and large student groups. The final product was used in a real teaching activity and it shows that students paid more attention on the product and involved actively in virtual lab activity.